IMPLEMENTATION EXPONENTIAL COMPARISON METHOD IN ASSESSING THE PERFORMANCE OF SCOUT MOVEMENT LEADERS - mudya, Ajrian Pra; Anggraeni, Dewi; Sahren, Sahren (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: The need for Performance Evaluation in Scout organizations is important to ensure that organizational goals are achieved and training standards are maintained. Performance evaluation helps in identifying strengths, weaknesses, as well as areas for improvement in training. The importance of the quality of performance of trainers in the Scout Movement cannot be underestimated, because they have a central role in guiding, training and providing inspiration to students. For this reason, there is a need to evaluate the performance of Scout trainers to increase the effectiveness of training and improve the quality of Scout education. The purpose of this research is to identify trainer performance quality criteria, evaluate their performance, and contribute knowledge in the development of a Scout trainer performance evaluation system. Then, the exponential comparison method (MPE) is used to provide a comprehensive assessment of the trainer's performance based on predetermined criteria. The results of this research are a web-based decision support application by applying the Exponential Comparison Method to evaluate the quality of Scout trainer performance, which can help improve the quality of training and provide guidance for Scout education providers. This research makes an important contribution to the development of a more efficient and effective Scout trainer performance evaluation system.         Keywords: coaching;  decision support systems; exponential comparison; performance. Abstrak : Kebutuhan akan Evaluasi Kinerja dalam organisasi Pramuka menjadi penting untuk memastikan bahwa tujuan organisasi tercapai dan standar pelatihan dipertahankan. Evaluasi kinerja membantu dalam mengidentifikasi kekuatan, kelemahan, serta area untuk perbaikan dalam pelatihan. Pentingnya kualitas kinerja para pelatih dalam Gerakan Pramuka tidak dapat dianggap rendah, karena mereka mempunyai peranan sentral dalam membimbing, melatih dan memberikan inspirasi kepada peserta didik. Untuk itu kebutuhan akan evaluasi kinerja pelatih Pramuka diperlukan untuk meningkatkan efektivitas pelatihan dan meningkatkan mutu pendidikan pramuka. Tujuan penelitian ini untuk mengidentifikasi kriteria kualitas kinerja pelatih, mengevaluasi kinerja mereka, dan menyumbangkan pengetahuan dalam pengembangan sistem evaluasi kinerja pelatih Pramuka. Kemudian, metode perbandingan eksponensial (MPE) digunakan untuk memberikan penilaian komprehensif terhadap kinerja pelatih berdasarkan kriteria yang telah ditentukan. Hasil dari penelitian ini sebuah aplikasi pendukung keputusan berbasis web dengan menerapkan Metode Perbandingan Eksponensial untuk mengevaluasi kualitas kinerja pelatih Pramuka, yang dapat membantu meningkatkan mutu pelatihan dan memberikan panduan bagi penyelenggara pendidikan Pramuka. Penelitian ini memberikan kontribusi penting dalam pengembangan sistem evaluasi kinerja pelatih Pramuka yang lebih efisien dan efektif.Kata Kunci: kinerja; pembinaan; perbandingan eksponensial; sistem pendukung keputusan